Cross-border Objectification: Implications for the objectified women in the East - Sreekanth, Yagnamurthy (Journal of Gender and Power, 2019)
Objectification theory says that females are socialized to think of their bodies as objects and to internalize an observer’s viewpoint of their bodies (Fredrickson & Roberts, 1997). While feminist literature in developed countries is profuse with objectification of women within their national boundaries, they ignore the objectification committed against women of other countries, and especially the developing countries. Although, Nussbaum has extensively dealt with objectification, her analysis and much of the literature on objectification, document intra-national rather than international objectification, which I describe as cross-border objectification. In cross-border objectification, objectifier traverses one’s national boundaries to perpetrate objectification. I explain the cross-border objectification of women with the example of Thailand, a developing country, and how it is swayed by the developed world. The characteristics of cross-border objectification surpass the features of ‘objectification’ as they are defined in the west. Some of the specific characteristics observed as part of cross-border objectification are—providing alternate means and access to financial gains in order to exploit them; old men seeking unsustainable pleasure and company of young women; and finally, transitory emotional and non-sexual/sexual relationships, betraying social relationships of an enduring society. Further, it is exacerbated through the malicious circle of communication and transportation-beautification-objectification. The issue of cross-border objectification requires a special attention of the international community and largescale empirical researchers are necessary to investigate the nature of the problem and how remedial actions could be initiated.